(untitled) (A Social Science and Entrepreneurship Journal, 2025)
This study aims to determine the effect of Facebook Social Media Marketing on Brand Awareness. The object of this study is the Ornamental Fish Lovers Micro, Small, and Medium Enterprises (MSMEs) at Starlite in Tasikmalaya City. This study uses a quantitative approach by collecting data through distributing questionnaires. The population in this study were followers of the Kamfa Louhan Lovers Tasikmalaya group. The sample in this study amounted to 100 respondents. The results of this study are that Facebook social media marketing has a positive and significant effect on brand awareness at Starlite. This is proven by the t-test and one-tailed test which states that the t-value is 20.443 > t-table 1.66055 with a significance level of 0.000 < 0.05. Itcan also be concluded that if Starlite’s social media marketing continues to improve, its brand awareness will also increase, and vice versa. Therefore, if Starlite continues to improve its social media marketing, it will help increase the number of people aware of the Starlite ornamental fish brand.